2020
DOI: 10.1002/jimd.12222
|View full text |Cite
|
Sign up to set email alerts
|

A missense variant remote from the active site impairs stability of human phosphoglucomutase 1

Abstract: Missense variants of human phosphoglucomutase 1 (PGM1) cause the inherited metabolic disease known as PGM1 deficiency. This condition is categorised as both a glycogen storage disease and a congenital disorder of glycosylation. Approximately 20 missense variants of PGM1 are linked to PGM1 deficiency, and biochemical studies have suggested that they fall into two general categories: those affecting the active site and catalytic efficiency, and those that appear to impair protein folding and/or stability. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
(173 reference statements)
0
3
0
Order By: Relevance
“…Both variants show a significant reduction in stability, with a T m approximately 6-7 C below that of the WT enzyme (Table 5). This decrease in stability exceeds that of 1-3 C seen for most other PGM1 missense variants (Lee et al, 2014), except for one remote from the active site that showed a >10 C reduction from the WT (Stiers et al, 2020).…”
Section: Variants Show Reductions In Stability and Increased Binding ...mentioning
confidence: 59%
See 2 more Smart Citations
“…Both variants show a significant reduction in stability, with a T m approximately 6-7 C below that of the WT enzyme (Table 5). This decrease in stability exceeds that of 1-3 C seen for most other PGM1 missense variants (Lee et al, 2014), except for one remote from the active site that showed a >10 C reduction from the WT (Stiers et al, 2020).…”
Section: Variants Show Reductions In Stability and Increased Binding ...mentioning
confidence: 59%
“…The T337M and G391V variant proteins characterized here represent the tenth and eleventh crystal structures of PGM1-CDG missense variants to be determined (Stiers et al, 2016(Stiers et al, , 2020Stiers, Graham et al, 2017;Stiers & Beamer, 2018a). Through its ability to accommodate significant perturbation, the robust, multi-domain structure of the enzyme has enabled detailed structural characterization of its variants, making this system a paradigm for understanding the molecular impacts of mutations related to inherited metabolic disease (Beamer, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation